Investigation of Furrow Formation by Rotary Tillage Tools with an Active Drive - M. A. Amantaev; R. I. Kravchenko; Ye. A. Zolotukhin; T. S. Tolemis; A. N. Tabuldenov (Сельскохозяйственные машины и технологии)
Power driven rotary tillage tools are widely used in agriculture. However, the process of furrow formation by these tillage tools remains insuﬃciently studied. (Research purpose) To study the process of furrow formation by the actuating elements of rotary working bodies with an active drive. (Materials and methods) The experiments were carried out on a laboratory setup in a soil bin filled with sandy soil. The attack angle of the working elements ranged from 30 to 90 degrees, and the kinematic parameter varied from 0.8 to 2.2. The actuating element of the investigated rotary tillage tools was made in both circular and elliptical blade forms with the least curvature line (the major semi-axis of the ellipse). The actuating element with an elliptical blade has the ability to adjust the angle of inclination relative to the axis of rotation of the of the tillage tool. (Results and discussion) Rotary tillage tools with a circular blade form a furrow parallel to the travel direction. It has been established that an increase in the attack angle of the tillage tool from 30 to 90 degrees results in a twofold increase in the width of the furrow. The actuating element, made along the elliptical line of the blade, forms a furrow having the shape of a parallelogram when viewed from above. At a small angle of attack, this actuating element forms a short, narrow furrow deviating from the unit’s travel direction within the boundaries of the furrow width of the rotary tillage tool. (Conclusions) The results obtained make it possible to choose the parameters for the studied rotary tillage tools, which will ensure the formation of optimal furrows. This will increase the evenness of the furrow bottom and the degree of weed destruction, i.e. improved soil quality.